La evolución de la industria en el País Vasco (Estudios humanísticos. Geografía, historia y arte, 1989)
The evolution of the industry in the Basque Country attracts our attention due to the current economic crisis. The Basque Country has gone from being considered an old and industrialised region to being considered by some a region in declive.